Pathogenic Fungal Infection in the Lung - Li, Zhi; Lu, Gen; Meng, Guangxun (Frontiers in Immunology, 2019)
Respiratory fungal infection is a severe clinical problem, especially in patients with compromised immune functions. Aspergillus, Cryptococcus, Pneumocystis and Candida are the major pulmonary fungal pathogens that are able to result in life-threatening invasive diseases. Growing number of studies have demonstrated that multiple cells and molecules orchestrate host defense against fungal infection in the lung. Upon fungal challenge, innate myeloid cells including macrophages, dendritic cells and recruited neutrophils establish the first line of defense through phagocytosis and secretion of cytokines. Natural killer cells control fungal expansion in the lung via direct and indirect killing of the invading organisms. Adaptive immune cells such as Th1 and Th17 cells confer anti-fungal activity via producing their signature cytokines interferon-γand IL-17. In addition, lung epithelial cells also participate in resistance against fungal infection by internalization, inflammatory cytokines production or antimicrobial peptides secretion. In the above mentioned host cells, various molecules with distinct functions modulate the immune defense signaling: Pattern recognition receptors (PRRs) such as dectin-1 expressed on cell surface are involved in the fungal recognition, adaptor proteins such as MyD88 and TRAF6 are required for transduction of signals to the nucleus for transcriptional regulation, inflammasomes also play essential roles in response to fungal infection in the lung. Furthermore, transcriptional factors regulate the expression of series of genes, especially those encoding cytokines and chemokines, which are predominant regulators in the infectious microenvironment, mediating the cellular and molecular immune responses against fungal infection in the lung.